Exit Exams and Stakeholders Engagement in Higher Education: Systematic Literature Review - Teshome, Samson Worku (International Journal of Humanities, Education, and Social Sciences, 2025)
Exit exams in higher education have been a subject of extensive research due to their potential impact on educational quality, student outcomes, and stakeholder engagement. This systematic literature review aims to explore the role of exit exams in higher education, focusing on stakeholder engagement, including students, faculty, administrators, and policymakers. Using the PRISMA framework, the researcher conducted a comprehensive search of academic databases, identifying 19 relevant studies to the topic. The review highlights the objectives, methods, and findings of these studies, with a particular emphasis on how stakeholders are engaged in the design, implementation, and evaluation of exit exams. The results indicate that stakeholder engagement is critical for the success of exit exams, yet it remains under-researched in many contexts. The review concludes with recommendations for future research and practice, emphasizing the need for inclusive stakeholder engagement strategies to enhance the effectiveness of exit exams in higher education.